2014
DOI: 10.22459/ag.21.01.2014.04
|View full text |Cite
|
Sign up to set email alerts
|

Is Academic Economics Withering in Australia?

Abstract: Departments of economics in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 12 publications
1
6
0
Order By: Relevance
“…Trends similar to those observed in the UK have been observed in other countries: Siegfried (2014) reports an increase in the demand for economics programmes In the US between 2007 and 2010, albeit one that appears to have stalled between 2011 and 2013; Lodewijks and Stokes (2014) uncover a similar picture of growing elitism in economics education in Australian universities. There is also evidence that the binary divide in the UK that the FHEA of 1992 was designed to remove may have reasserted itself, with new universities now offering more vocational course such as Business Studies, with their older counterparts focusing on more traditional academic disciplines such as Economics .…”
Section: Introductionsupporting
confidence: 62%
See 1 more Smart Citation
“…Trends similar to those observed in the UK have been observed in other countries: Siegfried (2014) reports an increase in the demand for economics programmes In the US between 2007 and 2010, albeit one that appears to have stalled between 2011 and 2013; Lodewijks and Stokes (2014) uncover a similar picture of growing elitism in economics education in Australian universities. There is also evidence that the binary divide in the UK that the FHEA of 1992 was designed to remove may have reasserted itself, with new universities now offering more vocational course such as Business Studies, with their older counterparts focusing on more traditional academic disciplines such as Economics .…”
Section: Introductionsupporting
confidence: 62%
“…the so-called Diamond list) are essential for a high rating to guarantee funding for future research (Lee et al 2013). It is believed by some that the Diamond list journals are open only to those with specialist training in econometrics and work against researchers working in areas that do not excel in econometric techniques (Lodewijks and Stokes 2014). In their attempt to get a higher rating, some universities may have moved out of the E&E UOA into the B&M UOA in the belief that they will achieve a higher rating and consequently boost research funding.…”
Section: Resultsmentioning
confidence: 99%
“…In this context, internationalisation is defined as the percentage of staff with overseas postgraduate qualifications. Several commentators have drawn attention to the increased Americanisation of Australian economics in the post-war period (Coleman, 2015;Lodewijks and Stokes, 2014). It was Groenewegen and McFarlane (1990) who first suggested that American-trained Australian economists '… did not seem to be aware of particular institutional, cultural and historical characteristics of the Australian economy' (p. 225).…”
Section: Discussion Of Findingsmentioning
confidence: 99%
“…A decade later, Lewis et al (2004) noted a decline in the tertiary-level numbers of economics students, and Abelson (2005) concluded that student standards had also declined. More recently, Lodewijks & Stokes (2014) have reported on the inevitable closure of economics departments across Australia, with many being subsumed into business schools and other faculties. Unsurprisingly, a desktop review of 39 Australian university websites in 2015 by Dobes et al (2016) identified only five undergraduate or postgraduate courses dedicated to CBA.…”
Section: Attrition Of Australian Public Service Expertise In Economicmentioning
confidence: 99%